Breaking Boundaries: Unveiling the Sociolinguistic Tapestry of Lavender Language Among Homosexuals in Region XI - Caminero, Mark Lorenze J.; Limpot, Marilou Y. (Eximia, 2024)
The study aimed to find out the phonological, morphological, and semantic variations of the Lavender language in the provinces of Region XI namely Davao del Norte (DDN), Davao Oriental (DOR), Davao Occidental (DOC), Davao del Sur (DDS) and Davao de Oro (DDO). The study utilized a qualitative research design employing textual analysis approach. Fifteen (15) research participants, consisting of homosexual teachers, took part in the study, selected through purposive and snowball sampling methods. The findings revealed variations in the Lavender language in the provinces of DDN, DOR, DOC, DDS, and DDO. Phonological variations included consonant clusters, phonemic changes, diphthongs, phoneme /ŋ/, and the use of accent marks on vowel phonemes. Morphological variations encompassed reduplication, coinage, and affixation, particularly prefixes, suffixes, and circumfixes. Semantic variations comprised words derived from the names of famous personalities, straight words, brands, food, places, and associated sounds. Overall, the results of the analyses shed light on how subgroups in society develop their own language to communicate with each other.